MODEL PENDIDIKAN ISLAM YANG BERWAWASAN HAK AZASI MANUSIA (HAM) - Sommeng, Sudirman (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2014)
The model of Islamic education that insightful human rights is based on the concept of fithrah who became normative provisions in developing and to optimize the use of the humanity.. This concept implies at least three things. First, the vision and orientation of the future education. Second, dealing educational purposes, and third, the materials and educational methodologies. Education (Islam) and human rights have a very close relationship, which can be seen functional relationships and symbiotic relationship.